Optimization of IEEE 802.11 parameters for wide area coverage - D Valerio; Luca De Cicco; Saverio Mascolo; Francesco Vacirca; T Ziegler (Proc. of MEDHOCNET, 2006)
Wireless mesh networks are quickly emerging as a solution for broadband wireless connectivity. The physical layer technology is making remarkable progress allowing higher bandwidth and longer distance coverage than before. While standardization efforts are going on to define new standards and paradigms for Wireless Mesh Networks, many vendors sell mesh solutions based on the 802.11b technology. This standard has been originally designed for Wireless Local Area Networks in indoor scenarios with a maximum distance between nodes up to few hundred meters. As a consequence, there are many technical challenges for adapting 802.11 to multihop networks and outdoor environments. This paper shows some guidelines to set the 802.11b MAC parameters in order to extend the coverage of 802.11 to long distance networks. Simulation results show that a fine tuning of MAC parameters can allow a satisfactory multi-hop wireless communication in mesh network scenario using 802.11.